Prognostic value of chronicity grading on renal outcomes in patients with IgA nephropathy - Kang, Donghyuk; Ban, Tae Hyun; Chin, Ho Jun; Lee, Hajeong; Oh, Se Won; Park, Cheol Whee; Yang, Chul Woo; Choi, Bum Soon (Frontiers in Medicine, 2022)
Many studies have shown that chronic changes are strong predictors of renal outcomes in various kidney diseases including IgA nephropathy. The Mayo Clinic/Renal Pathology Society suggested a glomerulonephritis reporting system with a proposal for standardized grading of chronic changes. The purpose of this study was to predict renal outcomes in patients with IgA nephropathy using chronicity grading in comparison to the Oxford classification which did not include global sclerosis. A total of 4151 patients with IgA nephropathy were enrolled from the Korean GlomeruloNephritis Study Group registry. Chronicity grading was categorized into minimal, mild, moderate, and severe according to the extent of chronic changes. The Oxford T and S scores were considered as chronic lesions. Three prediction models were constructed: the Oxford classification model (Oxford S plus T), chronicity grading model A (chronicity grading), and chronicity grading model B (chronicity grading plus Oxford S). Using three prediction models, the primary renal outcome (end-stage renal disease) was evaluated using Cox regression analysis and prediction performance. During the median follow-up of 6.1 (2.7-9.9) years, 304 (7.3%) patients progressed to end-stage renal disease with cumulative incidence rate of 1.02 events per 100 person-years. In a fully adjusted multivariable model, chronicity grading was independently associated with the primary renal outcome in both models A and B. Compared to the Oxford model, both models A and B showed improvements in model fit, but not in discrimination (ΔC 0.001; 95% CI, -0.010 to 0.013 and ΔC 0.002; 95% CI, -0.005 to 0.008, respectively). Model B demonstrated improvements in integrated discrimination improvement (0.01; 95% CI, 0-0.03) and continuous net reclassification improvement (0.49; 95% CI, 0.02-0.72). The severity of chronicity grading is closely related to adverse renal outcomes in patients with IgA nephropathy, and chronicity grading could provide additional information in clinical practice alongside the Oxford classification.